DINAMIKA AKTOR DAN KEBIJAKAN PUBLIK: STUDI IMPLEMENTASI PERATURAN DAERAH NOMOR 14 TAHUN 2010 TENTANG PAJAK MINERAL BUKAN LOGAM DAN BATUAN TAHUN 2011-2012 DI KABUPATEN SIAK - Armi, Irma Setiana; Anwar, Khairul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This study aims to describe the dynamics of the actors and the implementation of regional policies, especially government policies regarding taxes Siak Nonmetallic Mineral and rocks. As for the background of this research is the implementation of the policy has not been well. This study uses the theory of public policy implementation Grindle highlighting approaches in order to explain the phenomena encountered in the field. This study used qualitative methods, data collection techniques while using interviews, observation and discussion with sources of research. Furthermore, the data in the form of qualitative and quantitative data were analyzed with descriptive data analysis techniques.The results of this study indicate that the actors implementing the policy has not been able to implement the policy properly due to a lack of understanding of the policy. In addition, the lack of clear technical guidance and implementation guidelines also influence policy implementation. Actor supervisory board policy as well as the lack of a role in overseeing the implementation of policies. The condition is due kontens and difficult policy context dipamahi by implementing actors. The results of this study also indicate that the scope of the social interaction between communities, employers and the government has not been established. This is of course an impact on the political sphere that public support for the policy. While the economic sphere also no significant effect on the increase in local revenues and increased welfare of the community because of the scope of this policy on the taxpayer (employer)Keywords: Actor, interest and resources.